2011
DOI: 10.3102/0034654311413395
|View full text |Cite
|
Sign up to set email alerts
|

Mapping the Complexity of Public Pedagogy Scholarship

Abstract: The term public pedagogy first appeared in 1894 and has been widely deployed as a theoretical construct in education research to focus on processes and sites of education beyond formal schooling, with a proliferation of its use by feminist and critical theorists occurring since the mid-1990s. This integrative literature review provides the first synthesis of public pedagogy research through a thematic analysis of a sample of 420 publications. Finding that the public pedagogy construct is often undertheorized a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
162
0
7

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 264 publications
(180 citation statements)
references
References 132 publications
0
162
0
7
Order By: Relevance
“…Biesta develops a distinctive concept of public pedagogy. The concept has been used in educational scholarship in many ways (Sandlin et al 2011) that show not only broad diversity but also confusion of what 'public' might mean. Furthermore, the ways scholars have used the concept of public pedagogy stretch 'pedagogy' across a wide spectrum, from socialization to teaching in formal educational institutions (Rantala and Ripatti-Torniainen 2013;Sandlin et al 2009Sandlin et al , 2011.…”
Section: Introductionmentioning
confidence: 99%
“…Biesta develops a distinctive concept of public pedagogy. The concept has been used in educational scholarship in many ways (Sandlin et al 2011) that show not only broad diversity but also confusion of what 'public' might mean. Furthermore, the ways scholars have used the concept of public pedagogy stretch 'pedagogy' across a wide spectrum, from socialization to teaching in formal educational institutions (Rantala and Ripatti-Torniainen 2013;Sandlin et al 2009Sandlin et al , 2011.…”
Section: Introductionmentioning
confidence: 99%
“…Such research has revealed how gender structures the experience of students in school systems, and how the experience of schooling (re)produces gendered identities and divisions of labour. Reading self-help books is a form of 'public pedagogy' (McLean, 2013(McLean, , 2014Sandlin, O'Malley, & Burdick, 2011;Sandlin, Schultz, & Burdick, 2010;Wright & Sandlin, 2009), through which adults access resources from popular culture and learn without the involvement of educational institutions. Past studies of adult learning through related forms of popular culture have included those focused on women's experiences (Jarvis, 1999;Kapell & McLean, 2015;Wright, 2007), but gender differences in informal adult education have not been subject to empirical research in a manner parallel to work done in the context of schools and post-secondary institutions.…”
Section: Introductionmentioning
confidence: 99%
“…We reflect on "precisely how pedagogies are conceptualised and how these pedagogies are enacted" (Burdick and Sandlin 2013, p. 143) within these environments. As such, our examination of the public pedagogies of digital mental health is partly a response to the call from Burdick and Sandlin (2013) to offer clarity as to what is meant by pedagogy (see also Savage 2010;Sandlin et al 2011). Scholarship focused on informal sites of learning (Ellsworth 2002(Ellsworth , 2005, pedagogy writ large (Hickey-Moody et al 2010) or public pedagogy (Sandlin et al 2011), has drawn attention to the learning that takes place across a range of public sites and spaces.…”
Section: Digital Entanglements: Public Pedagogies Of Mental Healthmentioning
confidence: 99%